Convenient and mild protocol for preparation of α –trimethylsilyloxyphosphonates using sulfamic acid and their oxidation to α – ketophosphonates in the presence of N-bromosuccinimide - Mitragotri, Satish; Kulkarni, Makarand; Desai, Uday; Wadagaonkar, Prakash (Arkivoc, 2021)
A convenient and mild protocol was developed for the trimethylsilylation of α-hydroxyphosphonates using hexamethyldisilazane as the silylating agent in the presence of sulfamic acid (SA) as a heterogeneous solid acid catalyst in dichloromethane as the reaction medium. The utility of SA as the catalyst for deprotection of α-trimethylsilyloxyphosphonates to parent α-hydroxyphosphonates by making a switch to a protic solvent such as methanol was also demonstrated. Furthermore, the oxidation of α–trimethylsilyloxyphosphonates to corresponding α–ketophosphonates was achieved in excellent yields employing N-bromosuccinimide in the presence of catalytic quantity of AIBN.

Role of preparation parameters of Cu-Zn mixed oxide catalyst in solvent free glycerol carbonylation with urea - Charate, Shrinivas; Shinde, Suhas; Kondawar, Sharda; Desai, Uday; Wadgaonkar, Prakash; Rode, Chandrashekhar (Journal of the Indian Chemical Society, 2021)
Solvent-free carbonylation of glycerol with urea to glycerol carbonate (GC) was achieved over heterogeneous Cu-Zn mixed oxide catalyst. Cu-Zn catalysts with different ratios of Cu:Zn were prepared using co-precipitation (CP) and oxalate gel (OG) methods. As compared to CuO-ZnO(2:1) catalyst prepared by oxalate gel (OG) method, much higher conversion of glycerol and highest selectivity towards glycerol carbonate (GC) was achieved with CuO-ZnO_CP(2:1) catalyst. Physicochemical properties of prepared catalysts were investigated by using XRD, FT-IR, BET, TPD of CO2 and NH3 and TEM techniques. The effect of stoichiometric ratio of Cu/Zn, calcination temperature of CuO-ZnO catalysts and effect of reaction parameters such as molar ratio of substrates, time and temperature on glycerol conversion to GC were critically studied. Cu/Zn of 2:1 ratio, glycerol-urea 1:1 molar ratio, 145 degrees C reaction temperatures were found to be optimized reaction conditions to achieve highest glycerol conversion of 86% and complete selectivity towards GC. The continuous expel of NH 3 from reaction the mixture avoided formation of ammonia complex with CuO-ZnO catalyst. As a result of this, CuO-ZnO catalyst could be recycled up to three times without losing its initial activity.
Keywords: Co-precipitation (CP); Glycerol; Glycerol carbonate; Oxalate gel (OG)